Implikasi Pedagogis dalam Pendidikan Islam Anak Usia Dini pada Konsep Fitrah untuk Anak dalam Penafsiran Al-Qur'an Ibnu Katsir - Susan Sundari; Hafid Muslih (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
By considering both environmental and genetic factors, Islam offers an alternative for children's growth and development. Its pedagogical system for early childhood education creates a different understanding of the nature of the child. This study aims to reveal Ibn Katsir's concept of the nature of children through the Tafsir al-Qur'an al-'Aẓim. In addition, it aims to uncover the discourse between these two causes by analyzing debates in child development. This research uses qualitative methods with descriptive and analytical approaches. Data was collected through documents using Creswell's model analysis techniques. According to research conducted on the topic of human fitrah, fitrah as defined by Ibn Katsir is a positive and innate potential called Tawhid. This trait gives people the ability to act naturally without manipulation, which makes it essential for education to maintain. Education can study the actions of the prophet Muhammad through his stories and lessons. This is because Allah provided guidance through the messenger by teaching literacy and modeling. Additionally, education can use logic and data to learn through activities like classroom exercises. In order to receive the best result possible, children may utilize methods like Jidal or Mau'idhoh. Another option is to follow rote memorization and recitation with modeling from adults or teachers. Once necessary, the Fitrah can be utilized. In this case, it becomes a need for children to follow God's early promise to help shape their potential into a reality. This research also provides pedagogical practice based on Ibn Katsir's theory that children should be educated using Fitrah principles.